The complete chloroplast genome of Aloe vera from China as a Chinese herb - Jia-Ju Ren; Jian Wang; Kai-Ki Lee; Hui Deng; Han Xue; Nan Zhang; Jing-Chun Zhao; Tianyi Cao; Chang-Lei Cui; Xiu-Hang Zhang (Mitochondrial DNA. Part B. Resources, 2020)
Aloe vera has been used as a Chinese herb and an ingredient in many cosmetic products in China. In this study, the complete chloroplast genome of A. vera was determined for more genetic data information. The chloroplast genome was 152,875 bp length as a typical quadripartite structure that contained a large single-copy region (LSC) of 83,505 bp, a small single-copy region (SSC) of 16,178 bp and a pair of inverted-repeat regions (IRs) of 26,596 bp. The overall nucleotide composition of chloroplast genome is: 47,185 bp A (30.8%), 48,123 bp T (31.5%), 29,326 bp C (19.2%), 28,241 bp G (18.5%) and the total G + C content of 37.7%. Then, 131 genes were found that included 85 protein-coding genes (PCGs), 38 transfer RNA (tRNAs) and 8 ribosome RNA (rRNAs). The phylogenetic analysis showed that A. vera closely related to A. maculata in the phylogenetic relationship of the family Asphodelaceae by the Maximum-Likelihood (ML) method.